The metaphorical species: Evolution, adaptation and speciation of metaphors. (August 2015) - Domínguez, Martí
Studying cartoons about the economic crisis and focusing on a pair of scissors as a symbol, I prove how they first turn into unambiguous metaphor for the economic crisis and then experience an evolution in order to adapt to new communication contexts. Along these processes, they undergo more complex changes such as coadaptation and speciation. This has allowed for the scissors meme as a symbol of economic cutbacks to permeate society, and for its metaphorical use to occupy many disparate communication scenarios, unlike other symbolic elements that were also used, but turned out to be less cognitively efficient and therefore offered fewer evolutionary possibilities.